2018
DOI: 10.1002/ange.201705019
|View full text |Cite
|
Sign up to set email alerts
|

Von der Präzisionssynthese von Blockcopolymeren zu Eigenschaften und Anwendungen von funktionellen Nanopartikeln

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 186 publications
(114 reference statements)
0
2
0
Order By: Relevance
“…Snaith et al , prepared the synthesis of mesoporous TiO 2 film using as photoanodes of dye-sensitized solar cells. Steiner et al reported a series of inorganic materials in self-assembled polymeric templates for various applications. Lin et al innovatively synthesized monodisperse nanocrystal with various compositions and architectures by using starlike copolymers with well-defined structures and narrow molecular weight distributions as nanoreactors.…”
Section: Introductionmentioning
confidence: 99%
“…Snaith et al , prepared the synthesis of mesoporous TiO 2 film using as photoanodes of dye-sensitized solar cells. Steiner et al reported a series of inorganic materials in self-assembled polymeric templates for various applications. Lin et al innovatively synthesized monodisperse nanocrystal with various compositions and architectures by using starlike copolymers with well-defined structures and narrow molecular weight distributions as nanoreactors.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Among these, block copolymers provide unique advantages because of flexibility in structure variations, well-defined compartmentalized segments to form higher ordered structures and stable encapsulation of hydrophobic drug molecules. [13][14][15][16][17] But these systems also exhibit inefficient and incomplete drug release, which directly impedes their potential. Molecular release from block copolymer assemblies can be broadly classified into two approaches.…”
mentioning
confidence: 99%